1996
DOI: 10.1007/bf01894198
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of genitourinary fistulae in Kumasi, Ghana, 1977–1992

Abstract: The aim of the study was to determine the clinical epidemiology of genitourinary fistulae as seen at Komfo Anokye Teaching Hospital in Kumasi, Ghana. A retrospective study was carried out from the hospital records and operative reports of all patients with genitourinary fistulae seen at Komfo Anokye Teaching Hospital between January 1977 and December 1992. Patient age, parity, type of fistula and cause of fistula were abstracted from the medical records. There were 164 cases of genitourinary fistula managed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
2
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 15 publications
5
68
2
7
Order By: Relevance
“…Vesico vaginal fistula is well known late sequelae of prolonged obstructed labour. 16,17 In present study only 2 patients (0.8%) developed vesicovaginal fistula because of immediate and prolonged bladder catheterization and lesser incidence of destructive operation in our study. six maternal deaths occurred in our study due to extensive uterine rupture causing massive haemorrhage and hypovolemic shock and another 2-maternal death was due to septicemia and hence incidence of maternal mortality in our study was 3.5%.…”
Section: Discussionmentioning
confidence: 43%
“…Vesico vaginal fistula is well known late sequelae of prolonged obstructed labour. 16,17 In present study only 2 patients (0.8%) developed vesicovaginal fistula because of immediate and prolonged bladder catheterization and lesser incidence of destructive operation in our study. six maternal deaths occurred in our study due to extensive uterine rupture causing massive haemorrhage and hypovolemic shock and another 2-maternal death was due to septicemia and hence incidence of maternal mortality in our study was 3.5%.…”
Section: Discussionmentioning
confidence: 43%
“…[14][15][16] However, the divorce rate of 27% that was found in this work was much lower than the 55% earlier reported by Ibrahim et al [16] Prolonged obstructed labor remains the single most important cause of the fistula (85%) and has been demonstrated consistently in most reports from the West African sub-region. [3,9,14,15,17,18] Gishiri cut (traditional practice of cutting the vagina with sharp instrument) accounted for just two cases (1.5%) in this study when compared to the 13% reported from the Zaria area [5] or the 6.2% found at Maiduguri. [9] It is either because the practice of Gishiri cut is not common in the Sokoto area or that the incidence is falling with increasing awareness of its dangers.…”
Section: Discussionmentioning
confidence: 77%
“…Three out of every 1000 deliveries in West African countries develop VVF and about 200,000 women await surgical repair in Nigeria alone. [1][2][3][4] The prevalence of VVF is often underestimated because knowledge of the number of sufferers is linked to those who come to hospital for treatment. There are patients with the condition who suffer silence and isolation.…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect differing aetiology as previous studies have included women with fistulae secondary to gynaecological surgery and radiotherapy rather than purely obstetric causes 14 . Faecal incontinence has been reported in association with repair of a vesico-vaginal fistula but the frequency of this problem is unclear 3,8,9,13 . We have identified altered faecal continence in 21 women (38%) following repair of obstetric fistula, including women with frank faecal incontinence ( Table 2).…”
Section: Discussionmentioning
confidence: 99%